Examining New Directions In Media And Channel Seleclion In The Adopllon Process - Debrah H. Jefferson; Harian C. Lynn; James G. Shaner (Journal of Applied Communications, 1992)
Purpose: To expand the diffusion-adoption model to include the educational aspects of adoption and to refine thinking in terms of the channels used by adopters who seek information.